The Sociocultural and Demographic Determinants of Death Attitudes: A Comprehensive Review of Research in the Nepalese Context and Beyond - Adhikari, Hom Prasad; Pandit, Simran; Acharya, Sahara; Chaudhary, Niruta; Sedai, Pragati; Ojha, Sarina; Shrestha, Sarina (NPRC Journal of Multidisciplinary Research, 2025)
Background: Attitudes toward death are shaped by a complex interplay of psychological, cultural, and social factors. Recent research, particularly the work of Karki and colleagues in Nepal, has highlighted the importance of understanding these determinants within specific sociocultural contexts to address end-of-life care and mental well-being effectively.Objectives: This comprehensive review aims to synthesize the research on the sociocultural and demographic determinants of death attitudes, with a specific focus on findings from the Nepalese context. It further seeks to evaluate the methodological approaches and scholarly impact of this research domain.Methods: The review is based on a systematic analysis of literature identified primarily through Google Scholar and other academic databases, following standard systematic review and bibliometric analysis procedures. The methodology involved identification, screening, eligibility assessment, and final inclusion of relevant studies, with a particular emphasis on the quantitative cross-sectional research conducted by Karki et al. utilizing the Death Attitude Profile-Revised (DAP-R) scale.Findings: Research in Nepal reveals that death attitudes among youth and the elderly are significantly influenced by gender, cultural and religious beliefs, and social dynamics. Key findings include gender differences in neutral acceptance and death avoidance among youth, and the profound impact of family dynamics and living arrangements (e.g., family homes vs. elder care homes) on the death attitudes of the elderly. Bibliometric trends indicate a growing but fluctuating interest in this field.Conclusion: The perception of mortality is not universal but is deeply contextual. The consistent findings from Nepal underscore that sociocultural and demographic factors are critical in shaping how individuals approach death. A culturally sensitive understanding is therefore paramount.Implementation: The insights from this review can be implemented to develop targeted, culturally appropriate psychological interventions, educational programs, and support systems. These can help reduce death-related stigma and anxiety, and improve palliative and end-of-life care practices, particularly in diverse and under-researched cultural settings like Nepal.